2008
DOI: 10.1097/brs.0b013e318173dc8f
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Validation of the Argentinean Version of the Roland-Morris Disability Questionnaire

Abstract: The results of the study show that the Argentinean version of the RMDQ is reliable and valid as a lumbar disability measurement tool. The authors recommend this tool for future clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
15
23
0
Order By: Relevance
“…The test-retest reliability of the Korean version of the RDQ was excellent and the internal consistency, assessed by means of Cronbach's alpha was similar to the values present in other studies (17)(18)(19). There was a positive and moderate significant correlation between the RDQ and the NRS, coinciding with previous studies (17-19).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The test-retest reliability of the Korean version of the RDQ was excellent and the internal consistency, assessed by means of Cronbach's alpha was similar to the values present in other studies (17)(18)(19). There was a positive and moderate significant correlation between the RDQ and the NRS, coinciding with previous studies (17-19).…”
Section: Discussionsupporting
confidence: 78%
“…There was a positive and moderate significant correlation between the RDQ and the NRS, coinciding with previous studies (17)(18)(19). The convergent validity assessed by means of the correlation between the Korean RDQ and the Korean ODI was 0.758, very similar to the one reported in other studies (17,19). For responsiveness, in patients with chronic lumbar facet joint pain who underwent lumbar MBRF, the Korean RDQ with the higher area under the ROC curve showed a better overall responsive performance than did the Korean ODI.…”
Section: Discussionsupporting
confidence: 77%
“…The construction of the questionnaire was preserved, and the 24 items were maintained in a fashion similar to the original and other versions of the questionnaire. The Cronbach's alpha of 0.948 is a good measure of internal consistency of the Modern Standard Arabic version of the RMDQ, and is in accordance with other translated versions, 0.81 [8], 0.837 [9], 0.904 [13], 0.85 [14], 0.96 [15], 0.94 [16], 0.826 [19]. Positive correlation in the analysis for convergent validity was observed between both the RMDQ and FFL and VAS.…”
Section: Discussionmentioning
confidence: 50%
“…Studies that included mixed acute and chronic LBP patients reported higher correlations between the RMDQ and the VAS [9,17]. Some association with the spinal mobility measure may also be expected, although previous work is controversial regarding the existence of such association [12][13][14]16].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation